Czech (and other Slavic languages) against the background of Lotko's confrontational typology - Bogoczova, Irena (Bohemica Olomucensia, 2018)
The present article is a contribution to the confrontational typology of Slavic languages, and it extends the field of research (that the Czech polonist Edvard Lotko dealt with) by adding other language material, especially from the Russian language. The author of the article presents the typological differences between Czech and other Slavic languages gradually, i.e. on individual levels of the language system. She draws attention to the relevant differences and to the non-traditional approaches to the given issue contained both in domestic and foreign literature (Kucarov, Mrazek, Boskovic, Dudasova-Krissakova, etc.).
Keywords: Czech; Polish; Russian; language type; Edvard Lotko